(3GdLGeYs - (3eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj, CHh YHO Gddg, GdbQWHj,J (B671 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ bhdg JYGdi (B( (3hjSFdhfc Yf GdQhM (B) (3GdBjI ef ShQI GdGSQGA s
(3BNQgG (B:s
(3jfJgi CKfGA JaSjQ bhdg JYGdi (B( (3heG jfHZi ddQMef Gf jJNP hdOkG (B) (3GdBjI ef ShQI eQje s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B239s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B456 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B534s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs